A zirconium-free glaze system for sanitary ceramics with SiO2-CaCO3-TiO2 composite opacifier containing anatase: Effect of interface combination among SiO2, CaCO3 and TiO2. Issue 5 (May 2022) - Sun, Sijia; Ding, Hao; Ao, Weihua; Zhang, Baogang; Liu, Yangai; Zhang, Jianmeng; Zhang, Han; Li, Ming
Abstract: TiO2 is an ideal substitute to ZrSiO4 ceramic opacifier, yet it is limited to application because of the undesirable yellowing resulting from rutile formation. Herein, the SiO2 -CaCO3 -TiO2 composite opacifier (Si-Ca-Ti) was constructed. The glaze used Si-Ca-Ti presents a superior opacification performance than ZrSiO4 opacified glaze without causing yellowing, showing L*, a*, b* values of 94.81, -0.67 and 3.23. By comparison, the glaze using SiO2, CaCO3, and TiO2 mixture shows lower opacification and yellowish surface with L* and b* values of 92.99 and 5.36. It is revealed that there is a close interface bonding among SiO2, CaCO3 and TiO2 in Si-Ca-Ti, which promotes their combination reaction to generate opacification phase titanite and inhibit rutile formation when sintering, resulting in the white surface and opacification improvement of the glaze. This study proposes a green and efficient strategy to achieve white and highly opacified glaze for sanitary ceramics, exhibiting good application prospect.